ADDITIONS OF THREE HYPHOMYCETOUS FUNGI TO THE HYPHOMYCETES OF PAKISTAN - Sultana, Kishwar; Shahbaz, M. Umar; Irshad, Gulshan; Iqbal, M. Azhar (Comunicata Scientiae, 2014)
Hyphomycetous fungi Asteromyces cruciatus, a laboratory contaminant, Gyrothrix dichotoma from the fallen bottle brush branch and Wiesneriomyces javanicus from the deteriorating and decaying leaf of Holstonia scholaris a new host, were identified/ recorded for the first time from Rawalpindi, Pakistan.